2018
DOI: 10.1007/s11307-018-1251-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glucose Uptake and Uncoupling Protein 1 Activity in Adipose Tissue of Diabetic Mice upon β-Adrenergic Stimulation

Abstract: The metabolic response against adrenergic stimulation varied depending on the type of adipose tissue and DM. This could be important for the therapeutic activation of adipose tissue metabolism in obese diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The arcuate nucleus NPY regulates various physiological functions, including BAT thermogenesis (35). BAT contains abundant mitochondria and shows high expression of UCP1, which increase heat energy dissipation (36). Previous studies found that the Arc-specific NPY signaling pathway decreased sympathetically innervated BAT thermogenesis by down-regulating of UCP1 expression and BAT temperature (37).…”
Section: Discussionmentioning
confidence: 99%
“…The arcuate nucleus NPY regulates various physiological functions, including BAT thermogenesis (35). BAT contains abundant mitochondria and shows high expression of UCP1, which increase heat energy dissipation (36). Previous studies found that the Arc-specific NPY signaling pathway decreased sympathetically innervated BAT thermogenesis by down-regulating of UCP1 expression and BAT temperature (37).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity impairs b3-adrenergic agonist-dependent brown and beige adipocyte activation (Kubo et al, 2019;Shin et al, 2019). Next, we asked whether asparagine supplementation enhanced adipose tissue response to b3-adrenergic agonist in diet-induced obese mice.…”
Section: Asparagine Feeding Nourishes Thermogenesis In Adipose Tissuesmentioning
confidence: 99%
“…Additionally, Cypess et al con rmed the presence of adipose tissue such as brown fat in adult humans when exposed to cold [10]. BAT activation and WAT browning accelerates glycolipid intake, reduces the requirement for insulin secretion, and improves glycolipid metabolism and insulin resistance in patients with obesity and type 2 diabetes [11][12][13]. The thermogenic activity of BAT is largely dependent on uncoupling protein 1 (UCP1), which is present in the inner mitochondrial membrane.…”
Section: Introductionmentioning
confidence: 99%